2017
DOI: 10.1111/jiec.12643
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of State‐Ownership on Eco‐Innovations in Russian Manufacturing Firms

Abstract: This paper studies drivers for eco-innovation in Russian manufacturing firms on a sample of 2,212 innovative firms, of which over 600 introduced eco-innovations. The companies in our sample specifically mention environmental regulation as a reason for engaging in eco-innovations. Furthermore, we show that those firms who engage in eco-innovations are motivated even stronger by the desire to increase resource efficiency. Companies under state ownership are especially prone to a higher likelihood to invest. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 129 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…However, imperfect systems and shortsighted management can impede green transition. Our findings offer insights for promoting green transitions in developing nations with significant state ownership and environmental challenges (Roud and Thurner, 2018).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, imperfect systems and shortsighted management can impede green transition. Our findings offer insights for promoting green transitions in developing nations with significant state ownership and environmental challenges (Roud and Thurner, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…China, Russia and Brazil) and developed countries (e.g. France and the USA), providing competitive advantages for firms (Roud and Thurner, 2018). Although state ownership is not dominant in Western economies, it remains significant in several countries (Bruton et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The activities of the state corporations are indirect. The state uses indirect mechanisms of state participation through these legal entities in the implementation of public-private partnerships (Roud and Thurner, 2018). The analysis of the main features and characteristics of the state corporations revealed that they are a qualitatively new organizational and legal form in the Russian Federation.…”
Section: Resultsmentioning
confidence: 99%
“…Government funding of R&D for promoting energy saving mechanisms (Carrillo-Hermosilla et al, 2010;Guo et al, 2018;Jové-Llopis & Segarra-Blasco, 2018;Li et al, 2018;Yi et al, 2020) M7. Environmental regulation that stimulates win-win opportunities (Chang et al, 2019;Dewick & Foster, 2018;Feng & Chen, 2018;Gupta & Barua, 2018;Horbach et al, 2012;Jové-Llopis & Segarra-Blasco, 2018;Li et al, 2018;Roud & Thurner, 2018;Sanni, 2018;Tang et al, 2020;Wagner & Llerena, 2011) M8. Tax subsidy by government on environmentally friendly designs and products (Chang et al, 2019;Cooke, 2011;Díaz-García et al, 2015) M9.…”
Section: Round 3: Prioritisation Of Critical Network Factorsmentioning
confidence: 99%
“…Customer demands and preferences for environmentally friendly products (Horbach, 2016) M10. State ownership pressure on industries (Roud & Thurner, 2018) M11. Improving environmental efficiency for cost savings (Bossle et al, 2015) M12.…”
Section: Round 3: Prioritisation Of Critical Network Factorsmentioning
confidence: 99%